Volume 9: 23rd International Conference on Design Theory and Methodology; 16th Design for Manufacturing and the Life Cycle Conf 2011
DOI: 10.1115/detc2011-48306
|View full text |Cite
|
Sign up to set email alerts
|

Mechatronic Design - Still a Considerable Challenge

Abstract: Development of mechatronic products is traditionally carried out by several design experts from different design domains. Performing development of mechatronic products is thus greatly challenging. In order to tackle this, the critical challenges in mechatronics have to be well understood and well supported through applicable methods and tools. This paper aims at identifying the major challenges, by conducting a survey of the most relevant research work in mechatronic design. Solutions proposed in literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…For example, Torry-Smith et al [Torry-Smith et al, 2011] present a comprehensive literature review in which they identify nineteen reported engineering challenges. Of those nineteen, at least ten deal directly with communication.…”
Section: Practicementioning
confidence: 99%
See 4 more Smart Citations
“…For example, Torry-Smith et al [Torry-Smith et al, 2011] present a comprehensive literature review in which they identify nineteen reported engineering challenges. Of those nineteen, at least ten deal directly with communication.…”
Section: Practicementioning
confidence: 99%
“…In addition to the comprehensive review of [Torry-Smith et al, 2011], earlier work of the author [Haveman, 2009] has identified needs of system architects through a series of interviews with system architects at several companies developing complex systems (radar systems, medical devices, printers, consumer products). Here, eleven needs were identified of which five were classified as communication needs.…”
Section: Additional Needsmentioning
confidence: 99%
See 3 more Smart Citations